Government roles in enhancing exports: a study of the Ministry Of International Trade And Industry (MITI) Malaysia effectiveness / Shahirah Mohamad - Mohamad, Shahirah (Faculty of Business and Management, 2006)
The research is titled "Government Roles in Enhancing Exports: A Study of the Ministry of International Trade and Industry (MITI) Malaysia Effectiveness". The three objectives of the study is to examine the perceptions of exporters toward the roles played by the Ministry of International Trade and Industry (MITI) Malaysia, to examine the level of involvement between exporters and MITI, and to study MITl's effectiveness in promoting export. The scope of study was concentrated on the effectiveness of Ministry of International Trade and Industry (MITI) Malaysia in enhancing Malaysia export. The researcher used descriptive research as the research design and the sampling technique is probability sampling. This study more focused to exporter firms that dealing with MITI Pahang Branch and 40 respondents was selected to fulfill and completed the questionnaires. At the end of the study, based from the findings, it could be said that MITI Pahang branch is quite effective since most of the exporter has fully utilize the services provided by the government agencies and based from the findings several recommendations have been made for the organization and also for future research purpose.